Self-regulation training improves stress resilience in elite pre-pubescent female gymnasts - Proietti, G.; Borozan, M.; Chaigneau, A.; Cannito, L.; Palumbo, R.; Thouvarecq, R.; Iodice, P. (Frontiers in Psychology, 2024)
Introduction In the context of young female athletes, namely elite gymnasts, effective stress management strategies not only enhance performance, but also reduce the risk of injuries and promote overall well-being. This study aims to investigate the effects of biofeedback-based training on stress management in prepubescent elite female gymnasts, recognizing its pivotal role in promoting healthy growth and proper training load management.